2005
DOI: 10.1016/j.jcf.2005.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pseudomonas aeruginosa in patients with cystic fibrosis

Abstract: Chronic pulmonary colonisation with Pseudomonas aeruginosa (PA) in patients with CF is associated with a high morbidity and mortality. Adequate treatment of first acquisition of PA might prevent or postpone chronic colonisation. Early detection of PA is therefore of major importance. Currently, cultures of oropharynx or sputum are most commonly practised. However, oropharyngeal culture has limitations both in the positive and negative predictive value for the presence of PA in the lower respiratory tract. Indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 48 publications
1
33
0
3
Order By: Relevance
“…The negative association between inflammation and exercise capacity is compatible with the concept that chronic systemic inflammation results in a reduced exercise capacity due to devastating effects on skeletal muscle [32,34], which is not limited to CF disease [20] but is also present in other chronic inflammatory diseases, such as chronic obstructive pulmonary disease [29]. Skeletal muscle mass and function have been shown to be related to exercise capacity in CF [5,35], but were unfortunately not measured in our study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The negative association between inflammation and exercise capacity is compatible with the concept that chronic systemic inflammation results in a reduced exercise capacity due to devastating effects on skeletal muscle [32,34], which is not limited to CF disease [20] but is also present in other chronic inflammatory diseases, such as chronic obstructive pulmonary disease [29]. Skeletal muscle mass and function have been shown to be related to exercise capacity in CF [5,35], but were unfortunately not measured in our study.…”
Section: Discussionsupporting
confidence: 87%
“…Categorical data are presented as percentages. To evaluate whether CFTR genotype, chronic P. aeruginosa infection and inflammation were associated with longitudinal changes in exercise capacity in adolescents with CF, a multivariate linear mixed model (LMM) analysis for repeated measurements was used [32]. This statistical technique has several advantages: 1) subjects with missing data are not dropped from the analysis; and 2) within-subject changes and standard errors over time are calculated.…”
Section: Discussionmentioning
confidence: 99%
“…46 However, there is no reason for differential sensitivity of microbiology diagnosis between the two study groups.…”
Section: Limitationsmentioning
confidence: 96%
“…Serology as a diagnostic tool for nonmucoid P. aeruginosa detection or differentiation of nonmucoid from mucoid P. aeruginosa infection remains controversial, as there is no defined sequence of antigens or non-culture-based tests to aid in this distinction (13). Several studies have propagated serology and various antigens to diagnose initial P. aeruginosa infections (26,38,39,42). Ratjen et al (38) recently analyzed serum antibodies against alkaline protease, elastase, and ETA to define seroreactivity for the early diagnosis of P. aeruginosa infection in CF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies against these antigens were significantly higher in patients chronically infected with P. aeruginosa. TramperStranders et al (39) used the same antigens and reported that these specific antigens are more sensitive for the diagnosis of were separated by 12% SDS-PAGE. Proteins were transferred to PVDF membranes, blocked, and subjected to Western blotting with serum from three sequential blood samples drawn from patient 14 (referenced in Table 1).…”
Section: Discussionmentioning
confidence: 99%